Factors influencing employee turnover and retention strategies in the non-profit sector in Cape Town - Myburgh, Michelle (Department of Social Development, 2022)
Employee turnover can have devastating consequences on an organisation's efficiency and productivity, as it has cost implications, affects the human and social capital investment of an organisation, and can lead to employee burnout. Non-Profit Organisations (NPOs) provide valuable services in South Africa by addressing social and economic development issues. Should NPOs have a high employee turnover, it can impact their sustainability, growth, and performance. Consequently, this can influence the contribution they make to the social and economic development of the country. Retention strategies are used to prevent and combat employee turnover, with the aim of increasing organisational performance and sustainability. Therefore, the study sought to identify and explore the factors that lead to employee voluntary and involuntary turnover, the retention strategies NPOs use, and the effectiveness of these strategies. The study used an explanatory sequential mixed methods approach. The quantitative phase of this approach involved identifying current trends relating to staff turnover and retention strategies used by NPOs in Cape Town. The key themes that emerged through the quantitative phase of the study were explored in more depth by the qualitative phase of the study, providing a comprehensive understanding of the factors that contribute towards employee turnover and the retention strategies used to retain employees. The study's population was staff in leadership and/or management positions (CEO/Director and Human Resource Manager) at NPOs that provide social development services in Cape Town. The non-probability purposive sampling technique was used to draw a sample from the population for the quantitative phase of the study, of which 40 NPOs responded. The nonprobability purposive sampling technique was again used to draw a sample of 8 participants from the quantitative responses to participate in the qualitative phase of the study. The main findings of the research suggest that NPOs are aware that leadership styles and practices, and organisation culture and cohesiveness are strong contributing factors that lead to voluntary turnover, low performance, and deviant behaviour. NPOs experience that a goaldirected and people-orientated culture implemented by transformational leaders and organisational cohesive practices that make it clear what is expected of employees are the most effective ways of increasing employee motivation, satisfaction, commitment, and performance. Although these are strong retention practices, NPOs experience funding as a huge barrier to retain staff and implement retention strategies. In addition, NPOs implement strong stress reducing practices to address the emotional and psychological stress and burnout that is associated with NPO work. NPOs have a high focus on providing their employees with training and development opportunities to increase their performance but lack the ability to promote employees due to the size of the organisation. The findings suggest that NPOs are aware of the organisational factors that impact employees' performance, behaviour, and desire to leave. The effectiveness of retention strategies used by NPOs can be increased by addressing the barriers that prevent NPOs from implementing retention strategies.